Simulation of the heat accumulator operation of the internal combustion engine preheating system - Luniaka Klara (EDP Sciences, 2021)
We considered the heat accumulator with a phase-transfer heat-accumulating material, which serves for pre-heating of the car’s internal combustion engine. Simulation of the heat accumulator operation allows to build calculated graphs of temperature change of the heat-accumulating material in time, and afterwards to determine the charging time of the heat accumulator depending on its design features, thus, by modelling the most optimal design solution. We performed numerical computations of the system engine – circulating fluid – heat storage material – environment in two stages. In the first stage, we calculated the parameters of thermal resistance in the engine system and pipe manifold for different coolant temperatures according to the method of finite volume in the CFD system. In the second stage the problem was solved numerically by the method of equivalent thermal circuit. We carried out phase transition simulation using the Stefan condition, based on the thermal balance for the phase separation surface. We constructed numerical algorithmic models for calculations of temperature change of heat-accumulating material in time. Such calculations allowed determining the optimal number of U-shaped tubes based on which we proposed the heat accumulator design. We manufactured the heat accumulator, tested, and proved its efficiency and positive effect on the engine warm-up time and the passenger compartment.